Development of a methodology for building an information security system in the corporate research and education system in the context of university autonomy - Yevseiev, Serhii; Aleksiyev, Volodymyr; Balakireva, Svitlana; Peleshok, Yevhen; Milov, Oleksandr; Petrov, Oleksii; Rayevnyeva, Olena; Tomashevsky, Bogdan; Tyshyk, Ivan; Shmatko, Olexander (Eastern-European Journal of Enterprise Technologies, 2019)
The development of computing tools and technologies of corporate networks has expanded the range of educational and information services in corporate research and education networks (CRES). CRES belong to critical cybernetic information systems (CCIS) built on the basis of open network models. In the early 80s of the 20th century, this approach did not consider the need to build a security system, which does not allow it to provide the required level of protection against modern hybrid threats. The transition to autonomy in decision-making, education and university management all over the world places requirements to ensuring the required quality of service (QoS) of CRES clients. CRES users include university administration, faculty, students and support personnel of educational services in higher education institutions. One of the main criteria for QoS is information security. However, there is no general approach to building integrated information security in CRES, which would provide the required level of security. The methodology is based on the concept of synthesizing a synergistic model of threats to CCIS, improved models of CRES infrastructure, an intruder, assessing the current state of information security (IS) and improved method of investment in the CRES IS. It is shown that the basis of the synergistic model is a three-level model of strategic security management, which provides a synergistic effect in the context of simultaneous threats to information security, cybersecurity and security of information. In contrast to the known, such an approach provides for the determination of qualitatively new and previously unknown emergent properties of the information security system, taking into account the means used to create it. The application of the methodology in practice through the development and implementation of new solutions to provide security services allows for the required level of information security in CRES. The proposed information security service mechanisms are built on hybrid cryptosystems based on crypto-code structures with flawed codes.